If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9=-5v+2(v+3)
We move all terms to the left:
9-(-5v+2(v+3))=0
We calculate terms in parentheses: -(-5v+2(v+3)), so:We get rid of parentheses
-5v+2(v+3)
We multiply parentheses
-5v+2v+6
We add all the numbers together, and all the variables
-3v+6
Back to the equation:
-(-3v+6)
3v-6+9=0
We add all the numbers together, and all the variables
3v+3=0
We move all terms containing v to the left, all other terms to the right
3v=-3
v=-3/3
v=-1
| 6x+18-7=6x+3+x | | 4m+9=3 | | -6y+8(y-2)=-18 | | −(1+3)=8x1−4−2x1 | | 20=-8u+6(u+5) | | (7x-6)/3=6 | | 3x(x-5)-3x²=30 | | 4/2=n | | (12-3y)/6=(y-4)/2 | | 3/n=5 | | 3x-12=5x-28 | | 100x/2=60x-2 | | 32=4x+14 | | 20x/6-4x/3=2 | | 2x+10/4=8x-5/6 | | -u+184=54 | | -16+5x=4(3x=+7x) | | p²-6p+5=0 | | 203=-y+127 | | 0.5w=-35 | | 25÷3x-8÷5=9÷4 | | (25/3)x-8/5=9/4 | | x/6-x/12+5=x+5 | | 25/3(x)-8/5=9/4 | | 25/3x-8/5=9/4 | | .01(x+5)-0.05=0.01(6x+5) | | 1/2x-2=-3+2 | | 12x-4x+14=2x | | 227=-y+2 | | 227=-y | | 252-y=109 | | y/5-12=30 |